Low energy atomic field bremsstrahlung from thin rare gas targets - Semaan, M.E. (1982)
A relative measurement of the doubly-differential cross-section for electron atomic field bremsstrahling, differential in photon energy and angle is reported. Data for (d/sup 2/sigma)/(dk dO/sub k/) have been taken for incident electron energies T ranging from 4 to 10 keV on target atoms of helium, neon, argon, krypton and xenon at a photon emission angle of 90/sup 0/. The X-rays, produced at 90/sub 0/ to the intersection of the crossed electron and gas beams, are detected by a Si(Li) detector, having a resolution of about 200 eV at 6 keV and 0.3 mil Be window. The theoretical angular distribution (d/sup 2/sigma)/(dk dO/sub k/) has been deduced from the photon energy spectrum by the use of the shape function S(Z,T,k,T) defined by Tseng and Pratt as S(Z,T,k,T) = ((d/sup 2/sigma)/(dk dO/sub k/)) / ((dsigma)/(dk)). The values of S used were obtained by an interpolation of the benchmark data provided by Pratt et al. Agreement between our experiment and the theory is measured by how well the theoretical curve fits the data. The agreement appeared to be good.